Pengaruh Mind Mapping Terhadap Hasil Belajar Peserta Didik Kelas V Pada Mata Pelajaran Pendidikan Pancasila di SDN 14 Dalam Koto Surian - Hidayah, Mutia Puspa; Yelliza, Merri; Hendriyani, Maifit; Tulljanah, Rahmia; Kharisma, Annisa (Samsara Institute Publisher, 2025)
This study aims to determine the effect of the mind mapping method on the learning outcomes of fifth grade students in the Pancasila Education subject at SDN 14 Dalam Koto Surian. The background of this study is the low learning outcomes of students caused by the learning method which is still lecture-based and teacher-centered. This study uses a quantitative approach with a quasi-experimental method. The research design used is nonequivalent control group design. Data collection techniques are carried out through learning outcome tests. The results of the analysis show that there is a significant difference between the learning outcomes of students who use the mind mapping method and those who do not use it. Thus, the mind mapping method has a positive effect on improving student learning outcomesThis study aims to determine the effect of the mind mapping method on the learning outcomes of fifth grade students in the Pancasila Education subject at SDN 14 Dalam Koto Surian. The background of this study is the low learning outcomes of students caused by the learning method which is still lecture-based and teacher-centered. This study uses a quantitative approach with a quasi-experimental method. The research design used is nonequivalent control group design. Data collection techniques are carried out through learning outcome tests. The results of the analysis show that there is a significant difference between the learning outcomes of students who use the mind mapping method and those who do not use it. Thus, the mind mapping method has a positive effect on improving student learning outcomes.